Revisiting wage, earnings, and hours profiles - Peter Rupert; Giulio Zanella (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2014)
We document empirical life cycle profiles of wages, earnings, and hours of work for pay from the Panel Study of Income Dynamics, following the same workers for up to four decades. For six of the eight cohorts we analyze the wage profile does not decline with age (not before 65, at least), while the earnings profile always does. The discrepancy is explained by a sharp drop in the hours of work for pay profile beginning shortly after age 50, when many workers start a smooth transition into retirement by working progressively fewer hours. This pattern is not an artifact of staggered abrupt retirement, and is robust to attrition and selection-correction (i.e., taking into account that the composition of our sample, for a given cohort, changes over time). We explore the nontrivial restrictions on dynamic models of the aggregate economy that this evidence suggests, and we provide numerical profiles that can be readily used in quantitative macroeconomic analysis.
Keywords: E24; J13; J22; J24; J26; 330